Coatings and Surface Modification of Bioimplants - - 2, Theme (Recent Research in Science and Technology, 2010)
Proceedings of "Conference on Recent Advances in Biomaterials Dec 17-18 ’10" Held at Saveetha School of Engineering, Saveetha University, Thandalam, Chennai-602 105, Tamilnadu, India Theme 2 Coatings and Surface Modification of Bioimplants Â